Widekum Village Area Request by for Transfer from the Mamfe to the Bamenda Division (Colonial Letters and the Contact of Knowledges, 1964)
This file contains colonial letters on the Request by Widekum Village Area for Transfer from Mamfe to the Bamenda Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; Petitions; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies